Management Strategies in Building Learners’ Interest and Motivation Through the Package A, B, and C Equivalency Programs at PKBM Cahaya Ilmu Pekanbaru - Anisa Fitriani; Khalida Kirani; Nur Aini Safitri; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to describe the strategies of managers in building the interest and enthusiasm of learners through the Equivalency Education Program Package A, B, and C at PKBM Cahaya Ilmu Pekanbaru. PKBM Cahaya Ilmu is one of the oldest community learning centers in Riau Province, established in 2004, and has graduated more than one thousand learners. This study employs a qualitative descriptive approach, collecting data through in-depth interviews with the Chairperson, Administrative Staff, and Treasurer of the PKBM, as well as field observation and document analysis. The findings reveal that managerial strategies in building learners' interest and enthusiasm encompass four aspects: (1) program planning including scheduling, digital curriculum, and life skills programs; (2) learning implementation using flexible face-to-face, tutorial, and independent approaches; (3) guidance and mentoring processes through cross-subsidized tuition and information technology utilization; and (4) periodic evaluation and transparent financial management through the ARKAS system. Key challenges include negative public perceptions of equivalency education, lack of owned building, and financial dependency. These findings confirm that the success of equivalency programs is largely determined by managers' ability to design adaptive, inclusive, and learner-centered strategies.